Timbre, Genre, and Polystylism in Sonic the Hedgehog 3 - Megan Lavengood (Palgrave Macmillan, 2019)
In the soundtrack for the Sega Genesis game Sonic the Hedgehog 3 (1992), the genres represented include calypso, funk, carnival, new wave, prog rock, and more. Soundtracks for video games frequently shift genres this way, to create aesthetic themes for different levels or characters. Turning toward an account of the game’s soundtrack as a unified and continuous work, I posit that the music of Sonic the Hedgehog 3 might be understood as analogous to a series of “samples” within a polystylistic whole, following Leydon 2010. Leydon notes that instrumentation “bears the bulk of the semiotic burden” in communicating genre, but stops short of detailing how different instrumental timbres themselves might signify these genres. In my close analysis of two specific levels from Sonic the Hedgehog 3—Ice Cap Zone and Marble Garden Zone—I detail how timbre, as a musical parameter separate from instrumentation, can evoke specific inter-textual and extramusical associations from a listener, based on implied genres in the soundtrack. In doing this, I will show how timbre, a musical parameter that remains overlooked in a great deal of music analysis, might inform and en-hance dialogue in music analyses of genre within video game music and more broadly.